Design of demand management programs for the efficient use of electricity by industrial users (2017)
(Eng) Since October 2015 Colombia has suffered a shortage in the capacity to generate electricity due to the significant reduction in the levels of rainfall, a consequence of the climatic phenomenon of El Niño. The drought has caused a possible threat of rationing and the intervention by the regulator which is encouraging the voluntary reduction of energy consumption. This article proposes to use strategies for obtaining data known as ALL DATA to design demand management programs (DMP) in industrial users. It establishes that the data used must come from technical, economic, social and environmental aspects, so you can have a holistic aspect involved in the consumption of energy. In addition, it is proposed that the data obtained be supplied by the main agents that make up the marketing chain of electrical energy and finally, to identify the activities that would be developed by the DMP agent using the ALL DATA strategies to ensure the effective strategies in saving energy will continue over time.